An error analysis of the written English essays of the Bidayuh secondary school students / Misoi Nyilot @ Jiea Nyilot - Nyilot, Misoi @ Jiea (2011)
This study examines the errors in a corpus of 38 essays written by 38 participants. The participants are Form Four Bidayuh students who are studying at a secondary school in Bau. The samples, made up of 9 male and 29 female were selected from among the science students. They have experienced approximately the same number of years of education through primary and secondary education in Malaysia. All of the participants come from non-English speaking background and hardly communicate in English both inside and outside the school. The instrument used for this study was participants’ written essays based on the pictures-in-series after their elicitation test conducted. All of the errors in the essays were identified and classified into various categorisations. The results of the study show that five most common errors committed by the participants were developmental including omission, addition, use of inappropriate words, verb numbers disagreement, misordering and quantifier noun disagreement. Besides that, the study also shows there are inter-lingual, ambiguous and other types of errors. The data were analysed according to Corder (1974) in Ellis and Barkhuizen (2005).These aspects of writing in English pose the most difficult problems to the participants. This study has shed light on the manner in which students internalise the rules of the target language, which is English. Such an insight into language learning problems is beneficial to teachers because it provides information on the suggested taxonomies employed to address problems faced by the Bidayuh secondary school students in learning English as a second language (L2) which can be used in preparation of effective teaching materials. The findings of the study reveal that some errors committed by L2 learners derived from their mother tongue interference. The implications of the study include the needs for teachers to provide feedbacks with regards to erroneous language items made by the learners to prevent fossilization.